Review on the application of lateral flow chromatographic assay in Escherichia coli O157:H7 detection - TIAN Ge; JIANG Yijia; ZHANG Yun (Zhongguo shipin weisheng zazhi, 2024)
As a common foodborne pathogen， Escherichia coli （E. coli） O157：H7 can cause serious diseases in human body at low infectious doses. Lateral flow chromatographic assay （LFCA） can meet the requirement of detecting E. coli O157：H7 in food samples rapidly due to its efficient separation property. At present， the widely-used LFCA methods generate weak signal strength and possess low detection sensitivity， which can hardly detect low concentration of E. coli O157：H7. Therefore， this review focuses on the newly published LFCA literature， and a systematic induction is performed concerning the detection efficiency and sensitivity of the above studies. The advantages and disadvantages of each method are compared in this review， which will provide important conclusive guidance for the development of LFCA in E. coli O157：H7 detection.